2020
DOI: 10.3390/coatings10121234
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effect on Functionalized Silver-Based Nanocoating Braided Coronary Stents

Abstract: A previously developed fiber-based polyester (PES) stent, with mechanical properties comparable to commercial nitinol stents, was coated with metallic silver (Ag0) and silver oxides (AgxO) thin films through direct current (DC) magnetron sputtering. Ag0 and AgxO coatings provide antimicrobial properties to the stents to minimize the occurrence of coronary stent infections. Nevertheless, the stent interacts with the atmosphere and then with the biological fluids and may lead to the generation of silver species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…These species, especially ROS, have a high preponderance in cell death by some mechanisms, including DNA damage culminating in extensive mutagenesis that leads to irreversible damage and, ultimately, the loss of viability. The induction of an apoptotic-like process and the inhibition of essential metabolic processes are other mechanisms of cell death by means of ROS [ 54 , 55 ]. It is also reported that silver ions cause the separation of paired DNA strands in bacteria and weaken the bond between protein and DNA, and ROS are generated as a consequence of this phenomenon [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…These species, especially ROS, have a high preponderance in cell death by some mechanisms, including DNA damage culminating in extensive mutagenesis that leads to irreversible damage and, ultimately, the loss of viability. The induction of an apoptotic-like process and the inhibition of essential metabolic processes are other mechanisms of cell death by means of ROS [ 54 , 55 ]. It is also reported that silver ions cause the separation of paired DNA strands in bacteria and weaken the bond between protein and DNA, and ROS are generated as a consequence of this phenomenon [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, by being strongly entrapped in the hydrogel matrix, the active agent may not be effective in its vicinity. Unless it is able to perform an indirect antibacterial activity, such as the generation of reactive oxygen species, which will be released in the wound site and kill the invading bacteria (Rebelo et al, 2020).…”
Section: Contact-killing-based Hydrogelsmentioning
confidence: 99%
“…These NPs have robust antimicrobial activity, even at a low concentration. The silver ions can compromise cell wall integrity and generate reactive oxygen species (ROS) that effectively compromise genomic and proteomic activity, promoting cell death [16][17][18][19][20]. However, there is important evidence that they can be toxic to humans and cause environmental issues due to their low fastness to washing and other mechanical actions, such as rubbing [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%